(untitled) (Research, Society and Development, 2020)
Teeth displacement during extractions even tough rare are extremely unwanted, especially for infra temporal space. This accident generally necessitate additional treatment for their resolution, being either immediate or late. Several authors discribed surgical techniques for removal displaced teeth into the infratemporal space, varying according to the degree of displacement, being that in some of this cases, is necessary the utilization of complementary tools. This case describes the technique utilized for late removal of tooth 18 (upper right third molar) dislocated into the lower portion of the infratemporal space (confirmed by the Cone Bean Computer tomography Scan), exam was performed after the patient reported pain in the operated region and during mandibular movement too, with an interincisal opening maximum of 20 millimeters. The procedure was realized under local anesthesia by a conservative intraoral approach and aid of intermaxillary fixation screw to facilitate extraction. The patient recovered well, without complications, with remission of pain and restoration of mouth opening.